2006
DOI: 10.1002/cyto.a.20232
|View full text |Cite
|
Sign up to set email alerts
|

E‐LDL and Ox‐LDL differentially regulate ceramide and cholesterol raft microdomains in human Macrophages

Abstract: Atherosclerosis is characterized by the generation of lipidloaded macrophage-derived foam cells. To study the effect of different types of atherogenic lipoproteins, human macrophages were loaded with enzymatically degraded low density lipoprotein (E-LDL) or oxidized LDL (Ox-LDL). Cellular cholesterol content was increased by E-LDL, whereas Ox-LDL increased the ceramide content. Cell surface expression analysis by flow cytometry and confocal microscopy revealed that Ox-LDL increased ceramide and lactosylceramid… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 6 publications
1
37
0
Order By: Relevance
“…Glucosylceramide, lactosylceramide, and dihydroceramide correlated with plaque content of macrophages. The positive association between glucosylceramide and macrophages may be explained by the fact that glucosylceramide levels are high in human plaque monocytes as shown by Chatterjee et al 4 Accordingly, it has been shown that ox-LDL increases macrophage lactosylceramide synthesis, 15 but the association with lactosylceramide and macrophages may also be the effect of enhanced macrophage migration because of lactosylceramidedependent induction of adhesion molecule expression on monocytes and endothelial cells. 13 Because histological measurement of macrophages on cryosections from the 1-mm thick fragments of the most stenotic region of a plaque is a blunt, limited way to study inflammation, we also evaluated cytokine levels in the majority of the plaque tissue.…”
Section: Sphingolipids and Atherosclerotic Plaque Inflammationmentioning
confidence: 98%
“…Glucosylceramide, lactosylceramide, and dihydroceramide correlated with plaque content of macrophages. The positive association between glucosylceramide and macrophages may be explained by the fact that glucosylceramide levels are high in human plaque monocytes as shown by Chatterjee et al 4 Accordingly, it has been shown that ox-LDL increases macrophage lactosylceramide synthesis, 15 but the association with lactosylceramide and macrophages may also be the effect of enhanced macrophage migration because of lactosylceramidedependent induction of adhesion molecule expression on monocytes and endothelial cells. 13 Because histological measurement of macrophages on cryosections from the 1-mm thick fragments of the most stenotic region of a plaque is a blunt, limited way to study inflammation, we also evaluated cytokine levels in the majority of the plaque tissue.…”
Section: Sphingolipids and Atherosclerotic Plaque Inflammationmentioning
confidence: 98%
“…In order to characterize the modified LDL-preparations [43], ESItandem mass-spectrometry analysis of the lipid composition was performed for all LDL modifications derived from the same donor LDL, respectively.…”
Section: Cholesterol Cholesteryl Esters Oxysterols In Modified Ldlmentioning
confidence: 99%
“…Ceramide. Although the presence of ceramide in OxLDL has not been unequivocally demonstrated, oxidation of LDL is correlated with plasma ceramide levels (115), and the SM of OxLDL is more susceptible to hydrolysis by SMase (81). Conversely, SMase treatment of LDL increases its susceptibility to oxidation (271), and increases the aggregation of LDL and subsequent foam cell formation (249).…”
Section: Oxldl In Atherosclerosis and Autoimmune Diseasesmentioning
confidence: 99%